Calcium carbonate nanoparticles effects on cement plast properties - Safaei, Babak; Davodian, Erfan; Fattahi, A. M.; Asmael, Mohammed (Springer Heidelberg, 2021)
Cement plast or polymerized cement is a synthetic stone prepared using polymeric and nanomaterials which change the molecular structure of cement and minerals and create strong chain networks in cement due to polymerization reactions. In this work, the effect of the addition of calcium carbonate nanoparticles (NPs) on the mechanical properties of cement plast has been experimentally investigated. To do so, we investigated the effect of the addition of 0, 0.5, 1, 1.5, and 2 weight fractions of calcium carbonate NPs on the tensile and compressive strengths of cement plast samples. The experimentally obtained results showed that the addition of 1.5% calcium carbonate NPs improved the tensile strength of the samples by 20%. However, by further addition of calcium carbonate NPs, tensile strength was decreased by 22%. Based on the results obtained from the compression test, the addition of 2% calcium carbonate NPs improved the compressive strength of the samples by 25%. Also, the possibility of the prediction of the elastic modulus of the samples containing different percentages of calcium carbonate NPs by the developed theoretical method was evaluated.
Keywords: Nonclassical Plate Model; Mechanical-Properties; Portland-Cement; Free-Vibration; Buckling Analysis; Nano-Particles; Paste; Nano-Sio2; Concrete; Mortar